ONLINE LEARNING INCREASES TEACHER CAPACITY - Hetwi Marselina Saerang; Tinneke Evie Meggy Sumual; Elni Jeini Usoh (Jurnal Scientia, 2023)
Rene Descartes says, "cogito ergo sum (I think then I exist)". Man is always thinking about himself and his life. This is self-consciousness. Awareness about improving teaching capacity shows that nothing is permanent in human life but is constantly changing. Therefore, online learning is a thought process that varies from conventionality to professionalism. This change is called awareness of the identity of someone who becomes an educator according to the professional standards of a teacher in teaching and learning activities at school. Online learning forces teachers to increase capacity, especially in learning methods and media use. So far, teachers in Papua have always used conventional learning methods, namely face-to-face in class between teacher and student or lecturer with a student. The learning process, discussion, question-and-answer, and guidance are all controlled by a teacher. However, teachers must improve their professional capacity in teaching, such as no longer patronizing students, but dialogue with students. This change can be meaningful for the world of education in the Land of Papua, especially for young teaching staff, because they are a generation that grew up in this era of change. Meanwhile, elderly teachers are forced to run to adjust to the new way. Even if they seem deodorant, they must be ready to participate in change. What about elementary-level teachers, such as elementary and junior high schools, especially in rural areas? Of course, it will be fascinating because online learning is not only needed to improve quality, but it also takes the ability to operationalize this new way in learning design, it must also be equipped with IT pedagogy, because IT pedagogy itself has not been a raw material for teachers so far.